The strategic procurement practice guide : know-how, tools and techniques for global buyers - Weigel, Ulrich; Ruecker, Marco (Springer, 2017)
This practice guide on procurement strategy brings together methods and tools used by global purchasers across different industries. The authors lay major focus on the themes of global sourcing, risk management, and the dynamic topic of negotiation strategy. The authors present their perspectives on all important questions of strategic procurement such as: how to manage a heterogeneous supplier structure across different branches and how to deal with partners from diverse cultures? How to solve procurement crisis and proactively avoid them? How does off-shore team management work and how to increase the value-add for both internal and external purchasing? These themes are discussed along with numerous practice-based cases. The authors lay an ideal ground for global purchasers to help with their strategic and operational needs, including technological topics such as e-procurement.
Translation from the German language edition: Praxisguide Strategischer Einkauf.
Keywords: Purchasing.; Industrial procurement.; elektronické knihy; electronic books